Why Would I Befriend a Bot? Assessing Factors Influencing the Usage of Social Chatbots for Digital Natives - Mohammad Amin Kuhail; Jihene Mrabet; Rafiq Hijazi; Justin Thomas (Human Behavior and Emerging Technologies)
With advancements in artificial intelligence (AI), social chatbots (SCs) can now simulate meaningful, sympathetic interactions that blur the line between human and machine connection while also providing social and emotional support to its users. Generation Z (Gen Z), as tech-savvy digital natives, prefers individualized and emotionally engaging digital interactions, making them an important demographic for the adoption of AI-powered SCs. This study investigates the factors influencing Gen Z’s use of SCs, focusing on emotional support, attitudes towards AI, loneliness, and hedonic motivation. The study employed a quantitative survey with 156 participants who interacted with an SC and completed a questionnaire assessing key behavioral constructs. The findings reveal that emotional support and hedonic motivation significantly enhance trust in SCs, which in turn strongly predicts the intention to use them. To our surprise, loneliness had no measurable effect on the intention to use SCs, challenging assumptions that lonely individuals are more likely to adopt SCs. Privacy concerns similarly showed a negligible impact. These results highlight that fostering trust and providing enjoyable interactions are essential to promoting SC adoption among younger users.